2005
DOI: 10.1007/bf02889812
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-availability and speciation change of heavy metals in soils amended with lignin as micro-fertilizer

Abstract: Lignin is a primary byproduct from the black liquor treatment in paper making industries, its application as micro-fertilizer in agricultural land might provide a promising alternative to sewage discharge. However, application of such a micro-fertilizer might affect the soil properties and result in soil pollution. In this study, the effects of lignin application on phyto-availability and speciation change of heavy metals in soils were investigated. Greenhouse experiments showed that lignin application improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…78,79,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] It goes without saying that these two definitions can result in quite different interpretations of data. There are also a number of intermediate definitions in which the reducible fraction [203][204][205][206][207][208][209][210] or oxidisable fraction [211][212][213][214][215][216][217] was considered to represent the 'bioavailable/mobile' pool, either together with the easily extractable pool or on their own. Distinction is also made in some studies between the easily reducible pool (more mobile) and less easily reducible pool (less mobile).…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…78,79,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] It goes without saying that these two definitions can result in quite different interpretations of data. There are also a number of intermediate definitions in which the reducible fraction [203][204][205][206][207][208][209][210] or oxidisable fraction [211][212][213][214][215][216][217] was considered to represent the 'bioavailable/mobile' pool, either together with the easily extractable pool or on their own. Distinction is also made in some studies between the easily reducible pool (more mobile) and less easily reducible pool (less mobile).…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…Another possibility is that lignophenol is associated with chelating for overloaded Cu and Zn. Lignin seems likely to interact with a variety of metal ions (Claye et al 1996; Guillon et al 2001; Merdy et al 2002; Wang et al 2005; Mohan et al 2006). Zhuang et al (2003) developed a technology for the treatment of Hg‐contaminated water and soils by using lignin derivatives contain phenolic, carboxyl, sulfonyl, alcoholic and enolic structures, and confirmed that the lignin derivatives are capable of combining with other metal ions such as Cr, Cu, Pb, Zn, Ni and Al.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 In this context, research related to element mobility in fertilizer samples using the BCR sequential extraction protocol is predominantly focused on waste products used as soil amendments. However, most of these products are organic residues, such as sugar cane waste products, 20,21 byproducts from paper making industries, 22 and different types of sludge. 20,23−28 The purpose of these works is not only to evaluate the extraction of elements contained in soil amendments but also to verify the effect on the mobility of elements present in soils.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, research related to element mobility in fertilizer samples using the BCR sequential extraction protocol is predominantly focused on waste products used as soil amendments. However, most of these products are organic residues, such as sugar cane waste products, , byproducts from paper making industries, and different types of sludge. , The purpose of these works is not only to evaluate the extraction of elements contained in soil amendments but also to verify the effect on the mobility of elements present in soils. Soil evaluation demonstrates that potentially toxic element concentrations are generally higher and also more mobile in agricultural soils than in nonagricultural soils and that fertilization is one of the agricultural activities responsible for it . BCR sequential extraction was also employed to estimate Zn mobility in polluted soil with or without compost amendment, which its distribution and speciation within different organs of the edible plant were compared .…”
Section: Introductionmentioning
confidence: 99%